Intraoperative Detection of Leakage Using Topical Fluorescein Following Free Flap Inset in Head and Neck Reconstruction. Issue 4 (June 2019) - Cha, Han Gyu; Kwon, Jin Geun; Kim, Eun Key
Abstract : Abstract: In microsurgical head and neck reconstruction, a watertight closure following flap inset is essential to prevent saliva leakage and subsequent complications, such as wound dehiscence and fistulas. However, no standard method has been established to detect and localize the leakage following flap inset. The authors introduce a simple, easy, mobile, and inexpensive method to intraoperatively detect the leakage using topical fluorescein sodium mixed saline and Wood lamp. This simple procedure will allow surgeons to be confident of watertight closure.